An Analysis of Translation Procedures of Noun Phrases in Carlo CollodiÃ¢â‚¬â„¢s Novel Entitled Ã¢â‚¬Å“PinocchioÃ¢â‚¬Â - Anggraini, Nurul (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2018)
This research is conducted to identify the noun phrase and its types in Carlo Collodi’s novel entitled Pinoccio as well as procedures used to translate them in the translation version entitled Pinokio which was translated by Wiwin Indiarti. The data of this descriptive qualitative research are noun phrases found in the novel and their translation in Indonesian. Documentation is used to collect the data. Meanwhile, content analysis method is applied for analyzing data in relation to their contexts. The result of this research shows that there are 5.283 noun phrases in chapter 1 to chapter 36 of Pinochio novel. It is also found that there are 3 types of noun phrase. They are: 1) noun phrase type I which is identified as Modifier + Head (M+H) with 2.985 data, 2) noun phrase type II which is identified as Head + Modifier (M+H) with 425 data, and 3) noun phrase type III which is identified as Modifier + Head + Modifier (M+H) with 1.873 data. Furthermore, the translator used eleven translation procedures to translate noun phrases proposed by Newmark. Those procedures are 1) translation by Transference with frequency of 93 data (1.8%), 2) translation by Naturalization with frequancy of 102 data (2.1%), 3) translation by Cultural Equivalent with frequency of 308 data (6.2%), 4) translation by Functional Equivalent with frequancy of 97 data (1.9%) translation by Componential Analysis with frequancy of 773 data (14.7%), 6) translation by Synonymy with frequancy of 738 data (14.9%), 7) translation by Through-translation with frequancy of 1.205 data (24.3%), 8) translation by Shift or Transposition with frequancy of 792 data (17%), 9) translation by Compensation with frequancy of 438 data (8%). 10 translation by Couplets with frequency 173 (3.4%), and 11) translation by Modulation with frequency 43 (1%). It can be concluded that the translator often used Through translation procedure to translate noun phrases into Indonesian. It was used because she wants to deliver the message of the text as natural as possible